2020
DOI: 10.1007/s00344-020-10250-w
|View full text |Cite
|
Sign up to set email alerts
|

BnSIP1-1 Involves in Light Response and Regulation of Endogenous Hormones and Flowering Time of Brassica Napus

Abstract: BnSIP1-1 is a trihelix transcription factor family gene which functions in abiotic stress response and abscisic acid (ABA) signaling during seed germination and seedling growth of Brassica napus. In the present study, further sequence analysis and phenotype identification indicated that this gene had roles in light regulation and flowering of reproductive growth stage. Many phytohormones responsive cis-acting elements, including TC-rich repeats, GARE-motif, and TCA and TGA elements, were identified in the prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…With the release of the genome sequences of many plants, genome-wide identification of TH genes has been carried out in many species. However, other than for around 10 reported TH genes ( Table S10 ), the identification and the function of Brasscia TH genes, especially in B. napus , have not been well reported [ 5 , 16 , 17 , 18 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In this study, a total of 455 TH genes was identified in six Brassica species and Arabidopsis , and the phylogenetic relationship, structure, cis -acting elements, chromosome distribution, gene duplication events, and collinearity were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…With the release of the genome sequences of many plants, genome-wide identification of TH genes has been carried out in many species. However, other than for around 10 reported TH genes ( Table S10 ), the identification and the function of Brasscia TH genes, especially in B. napus , have not been well reported [ 5 , 16 , 17 , 18 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In this study, a total of 455 TH genes was identified in six Brassica species and Arabidopsis , and the phylogenetic relationship, structure, cis -acting elements, chromosome distribution, gene duplication events, and collinearity were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Positive T 3 generation plants were grown to produce cDNA libraries. The transgenic lines OE-7 and OE-27 overexpressing BnSIP1-1 were used for this study, in order to maintain consistency with previous research [ 13 , 24 ]. Lines OE-7 and OE-27 were used for phenotype characterization.…”
Section: Methodsmentioning
confidence: 99%
“…To have a better understanding how BnSIP1-1 reverses the trend of growth retardation caused by ABA in B. napus, tender seedlings were selected as the processing objects to obtain more sensitive data. Although there was no visible phenotype observed (Figure S1), we believed that many molecular level changes would be completely overturned based on our previous studies in BnSIP1-1-overexpressing B. napus [13,24]. Four-day-old seedlings of wildtype and transgenic plants treated with exogenous ABA were used for global transcriptomic analyses.…”
Section: Overview Of Transcriptome Sequencingmentioning
confidence: 99%
See 1 more Smart Citation